Assessing Financial Risks from Physical Climate Shocks : A Framework for Scenario Generation - Ranger, Nicola Ann (Washington, DC: World Bank, 2022)
Climate change has become a main concern of ministries of finance, central banks, and financial regulators. In response, a suite of scenarios and tools have been developed tthe potential scale of climate risks and underprice investments in resilience. This is particularly important for emerging markets and developing economies where exposure to physical climate risks is already high and is expected to further increase with climate change. The paper identifies five areas, or risk drivers, that make a material contribution to physical climate risks to the financial sector and that are not consistently included in current scenarios and tools: (1) extreme weather events; (2) uncertainties in climate models; (3) compound scenarios; (4) indirect economic impacts of shocks; and (5) feedback between the real economy and the financial sector. We derive a framework for generating scenarios to assess acute physical climate-related financial risks, which is inspired by the “Realistic Disaster Scenarios” that are used in risk management and supervision in the insurance sector. The framework is illustrated through an application of the EIRIN macroeconomic model. This framework aims to complement recent work by the Network of Central Banks and Supervisors for Greening the Financial System (NGFS) and the Financial Stability Board (FSB) to inform ministries of finance, central banks, financial regulators, and financial institutions on climate financial risk assessments, both for micro- and macroprudential risk management, and to incorporate climate risks into wider financial decision making and disclosures.o assess the financial risks from physical climate shocks (for example, hurricanes, droughts, wildfires, flooding). However, those scenarios do not fully capture such shocks, which could lead financial institutions to underestimate.